Legality on the acquisition of - Adriana Dragone Silveira; Vitor Mizuki (Universidade Estadual Paulista Júlio de Mesquita Filho, 2011)
This article aims to reflect upon the acquisition of "private educational systems" by cities in the state of São Paulo, under the perspectives of the standards listed in the "Constituição Federal de 1988" (CF/88), "Lei de Diretrizes e Bases da Educação Nacional" (LDB/96) and in the "Estatuto da Criança e do Adolescente" (ECA) and the actions that the Public Prosecutors Public Ministry have impetrated regarding to such acquisitions in the cities of São Bernardo do Campo and Barueri. The analysis of the normative principles indicates that the use of "private educational systems" interferes in the process of autonomy's pedagogical educational institution and also of the teachers and, in this way, restricts the principle of democratic management and the possibility of education to be taught from different pedagogical conceptions. From the analysis of the procedures instituted by the Public Prosecutors, it was observed that the actions were mainly concerned about Public Administration issues than educational legislation.